Pengaruh Likuiditas Dan Profitabilitas Terhadap Kebijakan Dividen Perusahaan Sub Sektor Perkebunan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2020 - Diah Feni Putri Pratiwi; Ida Siswatiningsih; Mawar Ratih Kusumawardani (Akuntansi, 2023)
This study aims to determine the effect of liquidity and profitability on dividend policy in plantation sub-sector companies listed on the IDX in 2015-2020. The data used in this study are the financial statement of the plantation sub-sector using annual data from 2015-2020. The sampling technique uses the purposive sampling technique. The statistical analysis tests used were the chow test, classical assumption test, panel data regression T-test, F-test, and the coefficient of determination. The test in this study uses Eviews 10. Based on the results of this study it shows that partially this research shows liquidity in the from of current ratio (CR)and profitability in the form of return on assets (ROA), return of equity (ROE), and net profit margin (NPM). Has no effect on dividend policyin the from of dividend payout ratio (DPR). Simultaneously the independt variables influence the dividend policy in the form of the dividend payout ratio (DPR).